Hubungan Lama Merawat dan Tingkat Pendidikan dengan Beban Keluarga Sebagai Caregiver dalam Merawat Pasien Penyakit Ginjal Kronik yang Menjalani Hemodialisis - Surani, Vincencius; Hardika, Bangun Dwi; Pranata, Lilik (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the relationship between length of care and level of education with the family burden as caregivers in caring for chronic kidney disease patients undergoing hemodialysis. This type of research uses an analytical survey with a cross sectional study approach. The sample in the study was 70 people using a simple random sampling method. Data were analyzed using the Spearman's Rank statistical test. The research results show that there is no relationship between the length of time caring for a patient and the burden on the family as a caregiver with a significance value of 0.428 > p value 0.05. There is no relationship between education level and family burden as a caregiver with a significance value of 0.793 > p value 0.05. In conclusion, the research results show that there is no significant relationship between length of stay and education on the family's burden as a caregiver. This shows that there are other factors that cause caregivers to experience a heavy burden when providing care to families undergoing hemodialysis. Keywords: Caregiver, Hemodialysis, Chronic Kidney